The Yellow house : Van Gogh, Gauguin and Nine Turbulent week in Arles - Gayford, Martin (London : Penguin, 2006)
Explores how differences in temperament between artist Paul Gauguin and Vincent van Gogh created an explosive form of inspiration for both while the two men lived together for nine weeks in 1988.
Keywords: Gauguin, Paul, -- 1848-1903. -- Friends and associates; Gogh, Vincent van, -- 1853-1890 -- Mental health